Pre-Service Mathematics Teachers Conceptions of the Constructivist Teaching and Learning Approach in the Colleges of Education Classrooms - , Evans Atteh (Archives of Current Research International, 2025)
The study sought to examine the perceived conceptions and effectiveness of the constructivist approach to teaching and learning among pre-service mathematics teachers on the development of problem-solving skills in the colleges of education. A survey design with a quantitative data was gathered for the study. Stratified sampling method was used to select 240 pre-service mathematics teachers in Ashanti and Western North regions of Ghana. The data collection had a response rate of 94.6% representing 227 pre-service mathematics teachers. The study employed both close-ended and open-ended questionnaire. The close ended questionnaire data collected were analysed using frequencies and percentages while the open-ended data were analysed using themes. The findings revealed that 88% of the pre-service mathematics teachers have good number of conceptions which constitute teaching acts that promote constructivism in a mathematics classroom. The findings also indicated that 80% of the pre-service mathematics teachers hold the view that constructivist approach of learning is effective on the development of students’ problem-solving skills in mathematics. The data again indicated that the pre-service mathematics teachers have adequate knowledge about the mathematics curriculum they are going to work with in the future, and the constructivist approach of teaching and learning was effective in promoting the development of pre-service mathematics teachers’ problem-solving skills. The study recommended that stakeholders of Teacher Education should put in place a scheme that will address the need to place emphasis of public examination on non-routine and real-life investigative problems in colleges of education to convince mathematics teachers on teaching through constructivism.